2021
DOI: 10.1167/iovs.62.12.5
|View full text |Cite
|
Sign up to set email alerts
|

U-Shaped Effect of Blood Pressure on Structural OCT Metrics and Retinal Perfusion in Ophthalmologically Healthy Subjects

Abstract: Purpose We wanted to investigate the association of blood pressure (BP) status with the ganglion cell-inner plexiform layer (GCIPL) and retinal nerve fiber layer (RNFL) thickness of nonglaucomatous eyes and to elucidate whether this effect is related to vascular metrics proxying retinal perfusion. Methods For this case-control study, we prospectively included 96 eyes of 96 healthy subjects (age 50–65) from a large-scale population-based cohort in the northern Netherland… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…Blood pressure was inversely associated with the inner retinal layers, which is in accordance with previous studies showing thinner inner retinal layers in persons with hypertension. 30 , 38 Further, we found that women with low blood pressure had thinner GCIPL compared to women with normal blood pressure. This corresponds to results in a recent publication, whereas as noted by the authors, the female proportion in their low blood pressure group was substantially higher than in the reference group with normal blood pressure, and this complicates the interpretation of their results.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Blood pressure was inversely associated with the inner retinal layers, which is in accordance with previous studies showing thinner inner retinal layers in persons with hypertension. 30 , 38 Further, we found that women with low blood pressure had thinner GCIPL compared to women with normal blood pressure. This corresponds to results in a recent publication, whereas as noted by the authors, the female proportion in their low blood pressure group was substantially higher than in the reference group with normal blood pressure, and this complicates the interpretation of their results.…”
Section: Discussionmentioning
confidence: 52%
“…This corresponds to results in a recent publication, whereas as noted by the authors, the female proportion in their low blood pressure group was substantially higher than in the reference group with normal blood pressure, and this complicates the interpretation of their results. 30 A strength of our study was that the sample size allowed sex stratified analyses, which seems important exploring this relationship possibly related to glaucoma risk. 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Moreover, an inverted U-shaped association was found between BP status and GCIPLT and RNFLT, and that both hypotension and hypertension were associated with thinning of the inner retinal layers. 18 However, most of these studies were cross-sectional in nature with small samples, and only a few longitudinal studies were conducted. To the best of our knowledge, no study has specifically analyzed the association between different BP metrics and longitudinal changes in RNFLT and GCIPLT.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Moreover, an inverted U-shaped association was found between BP status and GCIPLT and RNFLT, and that both hypotension and hypertension were associated with thinning of the inner retinal layers. 8 However, most of these studies were cross-sectional in nature with small samples, and only a few longitudinal studies were conducted. 5,7 To date, no study has specifically analyzed the association between different BP metrics and longitudinal changes in RNFLT and GCIPLT.…”
mentioning
confidence: 99%